Is the laparoscopic approach for rectal cancer superior to open surgery? A systematic review and meta-analysis on short-term surgical outcomes - Małczak, Piotr (Wideochir Inne Tech Maloinwazyjne, 2018)
INTRODUCTION: Over the past years the incidence of colorectal cancers has increased worldwide. Currently it is the most common gastrointestinal malignancy worldwide. The laparoscopic approach has become the gold standard for surgical treatment. However, a recently published meta-analysis showed no difference in short- and long-term oncological outcomes of laparoscopy for treating rectal cancer. AIM: To assess current literature on short-term outcomes of rectal cancer treatment using laparoscopic surgery in comparison to the open approach. MATERIAL AND METHODS: We performed a systematic review and meta-analysis according to the PRISMA guidelines. The primary outcomes of interest were morbidity and short-term complications. RESULTS: We identified 4,328 potential references. In the end we included 13 randomized controlled trials (RCTs). We did not find any significant differences in terms of morbidity, haemorrhage, ureter injury, anastomotic leakage, mortality, intra-abdominal abscess or postoperative ileus. We found significant differences in the rate of surgical site infections, operative time, blood loss, length of hospital stay and time to first bowel movement. CONCLUSIONS: This systematic review based on available RCTs confirms that laparoscopic rectal cancer surgery is associated with short-term outcomes comparable to the open approach. Moreover, in some aspects it provides better results (e.g. functional postoperative recovery, lower rate of surgical site infections (SSIs)). The quality of evidence is high; therefore in our opinion it is very unlikely that future trials will alter these results, and for this reason the laparoscopic approach can be considered the gold standard for the treatment of the majority of patients.